REPRESENTASI BUDAYA MINANGKABAU DALAM NOVEL NILAM JODOH YANG DIJEMPUT KARYA A.R. RIZAL - Marni, Laila; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2019)
This study was aimed to reveal the Minangkabau culture contained in the novel Nilam Jodoh Yang Dijemput and represent the culture with the condition of modern society. This study used a literary anthropological approach that cover seven elements of universal cultur. In collecting the data, the library study method is used. Data sources come were obtained from novel Nilam Jodoh Yang Dijemput. Data analysis used qualitative research with descriptive methods. Research that produce Minangkabau culture in the novel Nilam Jodoh Yang Dijemput complements of universal culture. (1) language is divided into 3 languages, (2) knowledge system the importance of education bench, (3) sosial organizations about the legal and marital system, (4) The equipment system is divided into 5 traditional equipment and 7 modern equipmen (5) livehood systems of 8 different professions, (6) Religious system contain of two data about the lebaran haji and malam takbiran, (7) The art believe into dance and music. The most data that found is about language.Keywords : Novel Nilam Jodoh Yang Dijemput, culture, literary antropology, representation, Minangkabau etnic